Improvement of Logical-Mathematical Skills Through Jumbo Snake and Ladder Games in Children Aged 5-6 Years - Dea Adelia; Ilhami, Akmillah (Yayasan Corolla Education Centre, 2025)
This study aims to improve the logical-mathematical abilities of children aged 5–6 years through the medium of Jumbo Snakes and Ladders games at Aisyiyah 12 Kindergarten, Palembang. The method used is the Kemmis & McTaggart model, Class Action Research (PTK), which consists of four stages: planning, action, observation, and reflection. The research lasted for one month with a collaborative approach between researchers and classroom teachers. Data is collected through observation and documentation, and analyzed to measure logical-mathematical indicators, such as number recognition, addition, subtraction, and reasoning. The results of the study show that the use of jumbo snakes and ladders games can increase children's enthusiasm for learning dengan tingkat pencapaian keberhasilan 18,5% dalam katagori Berkembang Sesuai Harapan dan 81,5% dalam katagori Berkembang Sangat Baik, sebelum di lakukanya tindakan 14,8%, meningkat menjadi 29,6% pada siklus l, dan pada siklus ll meningkat menjadi 81,5%. Peningkatan tersebut di lihat dari kondisi awal kemampuan logis-matematis anak di TK Aisyiyah 12 palembang yang berada pada katagori Berkembang Sangat Baik (BSB), sebelum di lakukanya tindakan mencapai 14,8%, meningkat menjadi 29,6% pada siklus l, dan pada siklus ll meningkat menjadi 81,8%. strengthen their understanding of basic mathematical concepts, and foster systematic thinking skills. This educational game has proven to be effective as a fun and interactive learning medium in the development of early childhood logical-mathematical intelligence.